PENGARUH KEPEMIMPINAN, BUDAYA ORGANISASI, DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN MUSI RAWAS UTARA - Mulyadi Mulyadi; Juliana Pratiwi; R A Zubaidah (LPPM UNIVERSITAS BINA INSAN, 2020)
The purpose of this study was to determine the Effect of Leadership, Organizational Culture, and Work Discipline on the Performance of Employees of the Public Works and Spatial Planning of North Musi Rawas Regency, both simultaneously and partially. The results obtained are: 1) partial test (t test) conducted proves that Leadership has a significant effect on the performance of the employees of the Department of Public Works and Spatial Planning of North Musi Rawas Regency. Organizational Culture has a significant effect on the performance of the employees of the Public Works and Spatial Planning Office of North Musi Rawas Regency. Work discipline has a significant effect on the performance of the employees of the Public Works and Spatial Planning Office of North Musi Rawas Regency. Leadership and Organizational Culture significantly influence the performance of employees of the Department of Public Works and Spatial Planning of North Musi Rawas Regency, as evidenced by, the calculated value of f = 9.010 is greater than the value of ftabel = 2.79. Organizational Culture and Work Discipline have a significant effect on the performance of the employees of the Department of Public Works and Spatial Planning of North Musi Rawas Regency, the value of fcount = 8071 is greater than the value of ftabel = 2.79. Leadership and Work Discipline have a significant effect on the performance of the employees of the Public Works and Spatial Planning Office of North Musi Rawas Regency, as evidenced by the calculated value of = 3.005 greater than the value of ftabel = 2.79. Leadership, organizational culture and work discipline have a significant effect on the performance of the employees of the Department of Public Works and Spatial Planning of North Musi Rawas Regency, as evidenced by the calculated value of = 5,897 which is greater than the value of ftabel = 2.79.